On the relation between Herder's idealism and his theory of the soul-body relationship - DeSouza, Nigel (Université d'Ottawa | University of Ottawa, 2016)
This paper explores the motivations behind and emergence of Herder's idealism. It posits that it is Herder's deep conviction in soul-body interaction and his conception of Bildung that are the underlying motives. Specifically, Herder develops an original version of idealism, based on the philosophical resources available to him, that grounds an intimate connection between the soul and body, which in turn provides the basis for an original epistemology that is the foundation of his theory of Bildung.
Keywords: Johann Gottfried Herder; Immanuel Kant; Leibniz; idealism; German philosophy; Enlightenment; soul-body interaction; Bildung